The first complete chloroplast genome of Glycine tabacina (Fabaceae) and its phylogenetic analysis - Xin Yin; Laipan Liu; Zhentao Ren; Qi Yu; Li Zhang; Wenjing Shen; Zhixiang Fang; Biao Liu (Mitochondrial DNA. Part B. Resources)
The complete chloroplast genome of Glycine tabacina (Labill.) Benth., a perennial legume native to southern China and the Pacific islands, was sequenced for the first time. The circular genome spans 152,842 bp, comprising a large single-copy (83,882 bp), a small single-copy (17,872 bp), and two inverted repeats (25,544 bp). It contains 128 genes, including 83 protein-coding genes. Phylogenetic analysis within the Glycine genus revealed two clusters, with G. tabacina closely related to G. dolichocarpa. This high-quality genome provides a foundation for future phylogenetic and conservation studies of G. tabacina.